National Saving and Financial Development in Asian Developing Countries - Graham J. Abbott (Asian Development Review, 1984)
National saving finances the bulk of investment in all but a few Asian developing countries, though the extent to which foreign savings (i.e., inflows of external financial resources) have been used to supplement national savings to finance investment has increased in several of these countries since the mid-1970s (see Table 1). This trend cannot be sustained. Foreign aid is not likely to increase at the rate experienced in the past while debt-servicing problems have reduced the capacity of most developing countries to raise loans in foreign capital markets. These countries will have to raise their national saving rates (the ratio of gross national saving to gross national product) if they want to keep their investment rates (the ratio of gross national investment to gross national product) at about the level they have averaged in recent years. But apart from this immediate consideration, higher national saving rates are needed to provide the basis for self-sustained growth and development…